2010
DOI: 10.1590/s0102-695x2010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Mimosa tenuiflora (Willd.) Poir. from Northeast Brazil against clinical isolates of Staphylococcus aureus

Abstract: RESUMO: "Atividade antimicrobiana de Mimosa tenuiflora (Willd.) Poir. do Nordeste do Brasil, contra isolados clínicos de Staphylococcus aureus". A Mimosa tenuiflora é uma planta nativa da região Nordeste do Brasil onde é conhecida como jurema-preta sendo amplamente utilizada na medicina popular. No presente trabalho a atividade anti-Staphylococcus aureus do extrato etanólico da M. tenuiflora foi avaliada pela determinação da concentração inibitória mínima (CIM), pelo método da diluição em agar, em 30 isolados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The results revealed that the extract successfully inhibited the growth of S. pyogenes , P. Mirabilis , S. sonnei , S. pyogenes, and Staphylococcus spp. Padilha et al [ 132 ] described the antibacterial activity of the EtOH extract of M. tenuiflora stem bark against S. aureus by using the minimum inhibitory concentration (MIC) with the agar dilution method and time-kill assay. At concentrations up to 4x MIC, only a bacteriostatic effect was observed, while at 8.x MIC a fast bactericidal effect was observed [ 133 ].…”
Section: Pharmacological Activities Of Genus Mimosamentioning
confidence: 99%
“…The results revealed that the extract successfully inhibited the growth of S. pyogenes , P. Mirabilis , S. sonnei , S. pyogenes, and Staphylococcus spp. Padilha et al [ 132 ] described the antibacterial activity of the EtOH extract of M. tenuiflora stem bark against S. aureus by using the minimum inhibitory concentration (MIC) with the agar dilution method and time-kill assay. At concentrations up to 4x MIC, only a bacteriostatic effect was observed, while at 8.x MIC a fast bactericidal effect was observed [ 133 ].…”
Section: Pharmacological Activities Of Genus Mimosamentioning
confidence: 99%
“…Its bark is widely used in traditional Mexican and Brazilian medicine as an effective remedy to treat skin burns and wounds [24,26]. This plant may be used to reduce venous ulceration [27]; accelerate the healing process [28]; act as an antimicrobial agent against Staphylococcus aureus [29], Micrococcus luteus, Bacillus subtilis, and Candida albicans [25]; and regenerate bone [30]. Several studies have isolated and identified the compounds present in different parts of M. tenuiflora.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus lemon ethanolic leaf extracts showed 61% inhibition rate for Alternaria sp. in a recent study [ 21 ]. In addition, chitosan nanoparticles coatings controlled successfully mycelial growth for Alternaria solani (72%) and Fusarium oxysporum (87%) in a study by Sathiyabama and Parthasarathy [ 29 ] therefore revealing the in vitro antifungal chitosan efficacy against these phytopathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chitosan nanoparticles coatings controlled successfully mycelial growth for Alternaria solani (72%) and Fusarium oxysporum (87%) in a study by Sathiyabama and Parthasarathy [ 29 ] therefore revealing the in vitro antifungal chitosan efficacy against these phytopathogenic fungi. The Mimosa plant extract previously described, during in vitro testing, showed a strong antimicrobial activity against human pathogens [ 17 , 21 ]. Llorens et al [ 26 ] discovered a novel function of this plant extract: enhancing the immune response to Sclerotinia plant pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation